Production and Partial Purification of Amylase By Aspergillus niger Isolated from Cassava Peel - A.K. Lawal,; A.M. Banjoko,; S.O. Olatope,; F.A. Alebiosu,; F.A. Orji,; Y.L. Suberu,; E.E. Itoandon,; K.A. Shittu,; O.D. Adelaja,; E. Ojo,; E.N. Dike,; G.N. Elemo, (Journal of Basic & Applied Sciences, 2014)
Aspergillus niger strains 1, 2 and 3 isolated from cassava dumpsites were used for the production of amylase enzyme. The Aspergillus niger strains 1, 2 and 3 had diameter (mm) zone of clearance of 17.0, 23.0 and 8.0 respectively using Potato dextrose agar plates fortified with starch. Studies on the amylase enzyme activity (mg/ml) of Aspergillus niger strains 1 and 2 showed 19,340 and 16,510 respectively. These values were higher than the commercially available amylase enzyme that had an activity of 5,722.2. The protein (mg/ml) and specific activity (units/mg) for amylase from Aspergillus niger strain 1 was 28.39 and 681.23 while 21.76 and 758.73 from Aspergillus niger 2 respectively. Purification using ammonium sulphate (% w/v) at 60, 80 and 100 on amylase enzyme from Aspergillus niger strain 1 for enzyme activity, protein and specific activity was 44405.49, 17.01 and 2610.55, 28949.76, 23.62 and 1225.65, 36220.25, 16.67, and 2172.787 respectively. The microbial production of Amylase enzyme in Nigeria from Cassava peel will reduce cost of production, convert cassava peel from waste condition to wealth, and will boost economy through indigenous industrialization.